(untitled) (Research, Society and Development, 2022)
This study aimed to evaluate the tooth after brushing with toothpaste containing or not active compounds and with different fluoride concentrations after erosion to establish and compare the effectiveness of each dentifrice in its use. Enamel, E (n=36) and dentin, D (n=36) bovine specimens were treated with artificial saliva (AS - control), fluoridated dentifrice (FD), 8% arginine (AR), and calcium silicate (CS). The samples (n=72) were subjected to cycles of demineralization (orange juice) followed by remineralization (saliva) and then tooth brushing (AR, FD and CS). The above cycle was repeated 3´/day for five days. Micro energy-dispersive X-ray fluorescence spectrometry (µ-EDXRF), roughness testing and scanning electron microscopy (SEM) were performed. The mean of roughness values (Ra, μm) were E-AS, 0.20; E-FD, 0.15; E-AR, 0.18; E-CS, 0.18; D-AS, 0.31; D-FD, 0.30; D-AR, 0.37; D-CS, 0.44. The SEM images showed a clear loss of tooth substance in AS and FD treatments. A significant positive mineral variation was observed on the dentin after brushed with AR (p<0.05). The FD dentifrice minimized the erosive effects of the orange juice. Arginine and calcium silicate could improve dental protection by the deposition of a surface layer of deposits. Different active compounds resulted in diverse degrees of protection regarding the type of substrate. The high concentration of fluoride and the inclusion of active compounds improves the dentifrice protection level.